2009
DOI: 10.1086/600302
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of O157 versus Non‐O157 Shiga Toxin–ProducingEscherichia coliInfections in Minnesota, 2000–2006

Abstract: Differences in severity among STEC infections could not be explained by stx2, suggesting that additional factors are important in STEC virulence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
90
4
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 26 publications
17
90
4
6
Order By: Relevance
“…This finding was previously described by many studies (37)(38)(39)(40). Among them, Hedican et al performed a sentinel surveillance of STEC infections in Minnesota and found 22 coinfected patients among 302 STEC-positive patients (40).…”
Section: Discussionsupporting
confidence: 76%
“…This finding was previously described by many studies (37)(38)(39)(40). Among them, Hedican et al performed a sentinel surveillance of STEC infections in Minnesota and found 22 coinfected patients among 302 STEC-positive patients (40).…”
Section: Discussionsupporting
confidence: 76%
“…In a work carried out in primates, the intravenous inoculation of stx2 produces HUS symptoms, while administration of the same dose of stx1 did not induce the syndrome (Stearns-Kurosawa et al 2010). Although stx2 is more toxic to humans, stx1 has also been attributed in severe illness such as HUS (Hedican et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Also in Spain, the majority of sheep STEC isolates was non--O157, with only 8.7% O157:H7-positive STEC (Oporto et al 2008). O157 STEC isolates are worldwide involved in different disease outbreaks in humans, while in recent years, outbreaks involving non-O157 isolates have been increasingly reported (Hedican et al 2009, Scheutz et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies suggest that non-O157 serogroups cause a similar but somewhat less severe range of clinical manifestations than O157 strains (28, 34,35). Retrospective analyses of patient clinical profiles from a U.S. hospital revealed similar incidences of bloody diarrhea and HUS in children presenting with either non-O157 (17 patients) or O157 (33 patients) infections (36).…”
Section: Observations From Human Outbreaksmentioning
confidence: 95%